âŠ•-s-extending modules - Al-Saadi, Saad A.; Al-Rubaye, Aya A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
The -s-extending modules will be purpose of this paper, a module M  is -s-extending if each submodule in M is essential in submodule has a supplement that is direct summand. Initially, we give relation between this concept with weakly supplement extending modules and -supplemented modules. In fact, we gives the following implications:Lifting modules   -supplemented modules   -s-extending modules  weakly supplement extending modules.It is also we give examples show that, the converse of this result is not true. Moreover, we study when the converse of this result is true.